2017
DOI: 10.1155/2017/7628175
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Assessment of Two Local Strains of the Beauveria bassiana (Bals.) Vuill. against the Tetranychus urticae (Acari: Tetranychidae) and Their Potential as a Mycopesticide

Abstract: This study was conducted to assess highly pathogenic Beauveria bassiana isolates to be used in biocontrol and to determine their potentials as mycopesticide. For this purpose, two B. bassiana isolates, which were locally isolated from T. urticae, were chosen. Firstly, three suspensions were investigated at the degree of humidity of 65 ± 5% and 100% RH. Secondly, these strains were selected according to their tendency to mass production, tolerance to UV radiation, and capability of producing spore at the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…In addition, solar UV radiation is perhaps the most harmful environmental factor affecting the viability of fungal spores (Moore, Bridge, Higgins, Bateman, & Prior, 1993). Ortucu and Algur (2017) also reported that there are sudden changes in both radial and spores production, especially in 30 and 60 min of UV-B application, as in our study. Oil-based formulations are reportedly able to significantly increase the tolerance of conidia to UV radiation, with improved germination of conidia, in comparison in traditional waterbased formulations (Alves, Bateman, Prior, & Leather, 1998).…”
Section: Entomopathogenic Fungi From Local Isolates Of Beauveria Andsupporting
confidence: 87%
See 2 more Smart Citations
“…In addition, solar UV radiation is perhaps the most harmful environmental factor affecting the viability of fungal spores (Moore, Bridge, Higgins, Bateman, & Prior, 1993). Ortucu and Algur (2017) also reported that there are sudden changes in both radial and spores production, especially in 30 and 60 min of UV-B application, as in our study. Oil-based formulations are reportedly able to significantly increase the tolerance of conidia to UV radiation, with improved germination of conidia, in comparison in traditional waterbased formulations (Alves, Bateman, Prior, & Leather, 1998).…”
Section: Entomopathogenic Fungi From Local Isolates Of Beauveria Andsupporting
confidence: 87%
“…However, the germination and growth rate are decreased or deteriorating rapidly over 30°C (Fransen, Winkelman, & Van Lenteren, 1987). Qazzaz, Al‐Masri, and Barakat (2015) and Ortucu and Algur (2017) reported that radial growth and spore production of five B . bassiana isolates at different temperatures started to decrease especially at 30°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…urticae , causing 63.31 percent mite mortality at a concentration of 0.3×10 8 conidia/mL [ 45 ]. In another study [ 46 ], found that the pathogenicity effects of the two different strains of B . bassiana on T .…”
Section: Discussionmentioning
confidence: 99%
“…63.31 percent mite mortality at a concentration of 0.3×10 8 conidia/mL [45]. In another study [46], found that the pathogenicity effects of the two different strains of B. bassiana on T. urticae were 24-60% on the third day, 62.7-88% on the fifth day, and 90.7-100% on the seventh day. According to [47], the percentage of T. urticae deaths ranged from 55 to 82%.…”
Section: Plos Onementioning
confidence: 92%